Financial System Management Resilience and Systemic Risk in Banking: Regulatory Perspective - Jonker Sihombing (Journal of Law, Politic and Humanities, 2025)
Study This will explore How authority regulation arrange management risk systemic in banking For ensure resilience system finance in a way Overall . Focus specifically on the framework regulation and role institution government in overcome risk Systemic . Method research used is legal normative . Results study show based on on the frame regulation and role institution government in overcome risk systemic , then Government , Bank Indonesia, Institutions Guarantor Deposits , and the Financial Services Authority Already coordinate with very close . Coordination This of course it fits with authority each . Bank Indonesia has the authority is in the field of policy monetary , policy macroprudential , and system payment , so that is done is control inflation , do stability mark swap rupiah , do decline interest rates , providing funds liquidity , loosening policy macroprudential , as well as guard smoothness system payment Good cash or non- cash . Institutions Guarantor Savings , as function guarantee savings , which do guarantee savings banking and settlement bank problematic . While Financial Services Authority , in accordance with his authority do regulation and supervision individual microprudential banking and industry non- bank finance , for ensure health each banks and institutions non- bank finance . From experience handling of COVID-19 in the past , then seen Bank Indonesia's authority according to the P2SK Law has role important in prevent and handle crisis system finance especially.